A New Life After Rebirth: An Aristotelian-Metaphysical Study of The Kurdish Mawlawi’s Poem “The Second Rebirth” and Raskolnikov, the Main Character in Dostoevsky’s Novel Crime and Punishment - Jaafar, Hamid Mustafa; Salih, Hersh Mohammed Saeed (Sulaimani Journal for Humanities, 2025)
Human beings, unique among creatures of earth’s surface, posses the remarkable ability of rebirth. This second chance, whether material or spiritual, is an exclusive gift to humanity. This process unfolds through shifts in attitude or by enduring a life marked by suffering and despair, ultimately leading to a state of purity – a fresh beginning. Literary works often explore this theme with delicacy and aesthetic sensibility. In this aspect, both Kurdish and world literature boast timeless masterpieces that delve into the transformative power of rebirth. This research focuses on two eminent figures of letters and connoisseurs: the Kurdish poet Mawlawi and the Russian novelist Dostoevsky. Mawlawi’s poem “One Day I Was Contemplating My Misfortunes”, succinctly and artistically portrays the rebirth process. In contrast, Dostoevsky’s magnum opus Crime and Punishment, illustrates this concept through the character of Raskolnikov; his journey toward renewal is protracted, involving introspection, and dictations till reaching a pivotal turning point of a profound and meaningful life. As a theoretical framework, this research employs Aristotelian Metaphysics to draw a revealing comparison between these two literary works. The research comprises an introduction, a conceptual framework, examinations of Mawlawi’s and Dostoyevsky’s perspectives, a comparative analysis, and finally a concluded section.
Keywords: Rebirth; New Life; Aristotlian Metaphysics; Mawlawi; Dostoyevsky